Rock Art and Sacred Landscapes
VIII, 284 p. 114 illus., 70 illus. in color.
Keywords: Social and behavioral scientists study religion or spirituality in various ways and have defined and approached the subject from different perspectives. In cultural anthropology and archaeology the understanding of what constitutes religion involves beliefs, oral traditions, practices and rituals, as well as the related material culture including artifacts, landscapes, structural features and visual representations like rock art. Researchers work to understand religious thoughts and actions that prompted their creation distinct from those created for economic, political, or social purposes. Rock art landscapes convey knowledge about sacred and spiritual ecology from generation to generation. Contributors to this global view detail how rock art can be employed to address issues regarding past dynamic interplays of religions and spiritual elements. Studies from a number of different cultural areas and time periods explore how rock art engages the emotions, materializes thoughts and actions, and reflects religious organization as it intersects with sociopolitical cultural systems. .